Pharmacokinetics of First-Line Antituberculosis Drugs in HIV-Infected Children with Tuberculosis Treated with Intermittent Regimens in India - Ramachandran, Geetha (Antimicrob Agents Chemother, 2015)
The objective of this report was to study the pharmacokinetics of rifampin (RMP), isoniazid (INH), and pyrazinamide (PZA) in HIV-infected children with tuberculosis (TB) treated with a thrice-weekly anti-TB regimen in the government program in India. Seventy-seven HIV-infected children with TB aged 1 to 15 years from six hospitals in India were recruited. During the intensive phase of TB treatment with directly observed administration of the drugs, a complete pharmacokinetic study was performed. Drug concentrations were measured by high-performance liquid chromatography. A multivariable regression analysis was done to explore the factors impacting drug levels and treatment outcomes. The proportions of children with subnormal peak concentrations (C(max)) of RMP, INH, and PZA were 97%, 28%, and 33%, respectively. Children less than 5 years old had a lower median C(max) and lower exposure (area under the time-concentration curve from 0 to 8 h [AUC(0–8)]) of INH (C(max), 2.5 versus 5.1 μg/ml, respectively [P = 0.016]; AUC(0–8), 11.1 versus 22.0 μg/ml · h, respectively [P = 0.047[) and PZA (C(max), 34.1 versus 42.3 μg/ml, respectively [P = 0.055]; AUC(0–8), 177.9 versus 221.7 μg/ml · h, respectively [P = 0.05]) than those more than 5 years old. In children with unfavorable versus favorable outcomes, the median C(max) of RMP (1.0 versus 2.8 μg/ml, respectively; P = 0.002) and PZA (31.9 versus 44.4 μg/ml, respectively; P = 0.045) were significantly lower. Among all factors studied, the PZA C(max) influenced TB treatment outcome (P = 0.011; adjusted odds ratio, 1.094; 95% confidence interval, 1.021 to 1.173). A high proportion of children with HIV and TB had a subnormal RMP C(max). The PZA C(max) significantly influenced treatment outcome. These findings have important clinical implications and emphasize that drug doses in HIV-infected children with TB have to be optimized.